Serum Copper, Zinc and Oxidative Stress in Patients with Psoriasis (Iraqi Journal of Medical Sciences, 2016)
Background: Psoriasis is a chronic inflammatory skin disease characterized by well-demarcated erythema and scaly plaques. The pathogenesis of psoriasis still remains unclear. An increased reactive oxygen species (ROS) and insufficient antioxidant activity associated with the pathogenesis of psoriasis lesions.Objective: To evaluate the link between oxidative stress parameters and some trace elements like zinc (Zn) and copper (Cu) ions with the pathogenesis of psoriasis disease.Method: Fifty patients with psoriasis were included in this study, 32 patients with localized psoriasis, and 18 with general psoriasis, another fifty healthy controls were included in this study. We measured serum malondialdehyde (MDA), super oxide dismutase (SOD), vitamins E and A, and Zn and Cu in patients and control subjects.Results: Serum MDA in total psoriasis patients (1.8±0.2 nmol/ml) was significantly higher than those of control (0.6±0.19 nmol/ml; p
Keywords: Psoriasis; Zinc; Copper; Oxidative Stress; malondialdehyde; super oxide dismutase